Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Pembelian dan Kepuasan Pelanggan Kedai Kopi Kimteng di Pekanbaru - Adhi Nurcahyo Achmad; Samsir Samsir; Yulia Efni (Bahtera Inovasi, 2020)
This study aims to see and determine the direct effect of the marketing mix on purchasing decisions and customer satisfaction. Research site at the Kimteng coffee shop Pekanbaru. The population in this study were all customers who made repeat purchases at the Kimteng coffee shop Pekanbaru. The sampling technique used was non-probability sampling using the simple random sampling method, because the sampling of members from the population was done randomly without paying attention to the strata in the population. Determining the number of samples 5 times the number of variable indicators as many as 30 are used. Thus, the number of samples to be studied in this study was 150 people. In this study, researchers will use SEM (Structural Equation Modeling) analysis. The results of this study indicate that there is a positive and significant influence between the marketing mix on purchasing decisions and there is a positive and significant influence between the marketing mix and purchasing decisions on customer satisfaction. Purchasing decisions are able to positively and significantly mediate between marketing strategies and customer satisfaction.